Genome-Wide Search for Genes Required for Bifidobacterial Growth under Iron-Limitation - Lanigan, Noreen; Bottacini, Francesca; Casey, Pat G.; O'Connell Motherway, Mary; van Sinderen, Douwe (Frontiers in Microbiology, 2017)
Bacteria evolved over millennia in the presence of the vital micronutrient iron. Iron is involved in numerous processes within the cell and is essential for nearly all living organisms. The importance of iron to the survival of bacteria is obvious from the large variety of mechanisms by which iron may be acquired from the environment. Random mutagenesis and global gene expression profiling led to the identification of a number of genes, which are essential for Bifidobacterium breve UCC2003 survival under iron-restrictive conditions. These genes encode, among others, Fe-S cluster-associated proteins, a possible ferric iron reductase, a number of cell wall-associated proteins, and various DNA replication and repair proteins. In addition, our study identified several presumed iron uptake systems which were shown to be essential for B. breve UCC2003 growth under conditions of either ferric and/or ferrous iron chelation. Of these, two gene clusters encoding putative iron-uptake systems, bfeUO and sifABCDE, were further characterised, indicating that sifABCDE is involved in ferrous iron transport, while the bfeUO-encoded transport system imports both ferrous and ferric iron. Transcription studies showed that bfeUO and sifABCDE constitute two separate transcriptional units that are induced upon dipyridyl-mediated iron limitation. In the anaerobic gastrointestinal environment ferrous iron is presumed to be of most relevance, though a mutation in the sifABCDE cluster does not affect B. breve UCC2003's ability to colonise the gut of a murine model.